Three new free-living nematode species (Nematoda, Enoplida) from mangrove habitats of Nha Trang, Central Vietnam - Tchesunov, A. V.; Mokievsky, V. O.; Nguyen Vu Thanh (Russian Journal of Nematology, 2010)
Three new nematode species of the order Enoplida were found in a degrading mangrove biotope in the Bay of Nha Trang, Central Vietnam. Admirandus belogurovi sp. n. (Oncholaimidae), a second species of the genus, differs from the only other species, A. multicavus Belogurov et Belogurova, 1979, in having shorter spicules (41-49 vs71-110 µm) and some measurements, as well as presence of a small midventral preanal supplementary papilla. Diagnosis of the genus Admirandus Belogurov et Belogurova, 1979 is emended. Tripyloides caudaensis sp. n. (Tripyloididae) is close to a group of species T. gracilis (Ditlevsen, 1918), T. marinus (Bütschli, 1874) and T. pallidus Tchesunov, 1981 with partly overlapped measurements and differs from them in shape of the tail consisting of distinct proximal conical and distal slender cylindrical portions and from T. pallidus additionally by oviparity vs viviparity. An annotated list of eleven valid species and a pictorial key for identification of Tripylodes species are given. Litinium subterraneum sp. n. (Oxystominidae) is characterised by the position of the amphideal fovea closely behind the circle of twelve anterior setae and presence of two preanal supplementary papillae. Litinium subterraneum sp. n. differs from the related L. aequale Cobb, 1920, Litinium sp. 1 and Litinium sp. 2 (both latter unnamed species were found in mangroves of Vietnam, Quang Ngo Xuan et al., 2008) in body length, relatively longer tail, position of the amphideal fovea, relative pharynx length, different distance from the cephalic apex to the ventral pore. Some data on microscale distribution of three species in mangrove intertidal zone are provided.